Happiness and education - Noddings, Nel (Cambridge University Press, 2003)
"This book explores what we might teach if we were to take happiness seriously as an aim of education. It asks, first, what it means to be happy and, second, how we can help children to understand what happiness is. It notes that, to be truly happy, we have to develop a capacity for unhappiness and a willingness to alleviate the suffering of others. Criticizing the current almost exclusive emphasis on economic well-being and pleasure, it discusses the contributions of making a home, parenting, cherishing a place, the development of character, interpersonal growth, finding work that one loves, and participating in a democratic way of life. Finally, it explores ways in which to make schools and classrooms happy places."--Jacket.